The Impact of Environmental Management Accounting on Sustainable Business Outcomes: Quantitative Evidence from Multinational Corporations - Rahmawati, Yunaita; Amri, Muhtadin (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: This research examines the impact of Environmental Management Accounting (EMA) on sustainable business outcomes in multinational companies. There is a knowledge gap regarding the specific influence of EMA on various sustainability performance indicators. Research Methods: This study uses quantitative methods by analysing data from 50 multinational companies listed on the stock exchange during the period 2018-2023. Results: The results show that the implementation of EMA has a positive and significant impact on energy efficiency and carbon emission reduction, but has no significant impact on green product innovation. Companies that integrate EMA into their operations show a 15% increase in energy efficiency and a 10% decrease in carbon emissions compared to companies that do not implement EMA. There is no strong evidence that EMA significantly drives green product innovation. Conclusion: These findings suggest that EMA can be an effective tool for multinational companies to improve sustainability performance through more efficient resource management and reduced environmental impacts.